Intraspecies competition among Salmonella enterica isolates in the lettuce leaf apoplast - Jacob, Cristián; Student, Joseph; Bridges, David F.; Chu, Weiping; Porwollik, Steffen; McClelland, Michael; Melotto, Maeli (Frontiers in Plant Science, 2024)
Salmonella enterica is a highly diverse species with distinct structural and functional features that contribute to its ability to thrive in a variety of niches. One of the niches is the phyllosphere. Multiple S. enterica serovars and strains have been reported to be able to persist inside the foliar tissue of lettuce (Lactuca sativa L.), potentially resisting washing steps and reaching the consumer. Lettuce has been linked to several bacterial disease outbreaks in humans in the past decades. Intraspecies variation of the bacterial pathogen and of the plant host can both significantly affect the outcome of foliar colonization.However, current understanding of this phenomenon is still very limited. In this study, we evaluated the capacity of 14 genetically barcoded S. enterica isolates to persist and compete in the leaf apoplast of two lettuce cultivars that have differing responses to bacterial colonization. These assays revealed that strains of S. enterica can substantially differ in their ability to survive and compete in a co-inhabited lettuce leaf apoplast. The differential foliar fitness observed among these S. enterica isolates might be explained, in part, by their ability to utilize nutrients available in the apoplast and to evade plant immune responses in this niche.